Death Penalty and Right to Life: A Comparison between International Bill of Human Rights and Islam - Mahdi Muhammad; Kem Nori Alfath; Yusuf Saefudin (Kosmik Hukum, 2023)
In human history, the death penalty is not a brand-new form of punishment. In early civilizations, it was known and widely used throughout the world. It was legalized in Codex Hammurabi. Contrary to its long history, the view changed radically after World War II. The abolition of it began to be propagated during the Universal Declaration of Human Rights (UDHR) formulation in 1948 due to respect for the right to life. Islam adheres to the fundamental principle that everyone has the right to life, but that does not mean there is no death penalty in Islam. In this research, the problem to be solved is whether the death penalty regulation, according to the International Bill of Human Rights and Islam, has accommodated the right to life. The purpose of it is to find out and analyze which death penalty regulatory regime is more accommodating to the right to life. This type of research is normative juridical research using secondary data consisting of primary and secondary legal materials. The approaches used are statute and comparative approaches. This research shows that the right to life is thoroughly accommodated in the Islamic death penalty regulation, while the abolition of it under the mandate of the International Bill of Human Rights, especially the Second Protocol to International Covenant on Civil and Political Rights, only accommodates the perpetrator right to life of the perpetrator by ignoring many people right who could potentially be taken away if they are not sentenced to death.Keywords: right to life, death penalty, Islam.